Expressions of isopeptide bonds and corneodesmosin in middle ear cholesteatoma. (21st July 2016) - Koizumi, H.; Kawaguchi, R.; Ohkubo, J.‐I.; Ikezaki, S.; Kitamura, T.; Hohchi, N.; Hashida, K.; Suzuki, H.
Abstract : Objective: Isopeptide bonds form cross‐links between constituent proteins in the horny layer of the epidermis. Corneodesmosin (CDSN) is a major component of corneodesmosomes, which bind corneocytes together. Both play important roles in maintaining epidermal barrier functions. In the present study, we investigated the expressions of isopeptide bonds, CDSN, and related enzymes in middle ear cholesteatoma in comparison with the skin. Design: Prospective case series of patients with middle ear cholesteatoma. Setting: Tertiary medical institute. Participants: Cholesteatoma and normal postauricular skin were collected from patients with acquired middle ear cholesteatoma during tympanomastoidectomy. Main outcome measures: Expression of e‐(g‐glutamyl)lysine isopeptide bonds was examined by immunohistochemistry; Expressions of transglutaminase (TGase)1, TGase2, TGase3, and TGase5 by immunohistochemistry and quantitative RT‐PCR (qRT‐PCR); expression of CDSN by immunohistochemistry, qRT‐PCR, and Western blot; and expressions of tissue kallikrein‐related peptidase (KLK)5, KLK7, KLK14, and serine peptidase inhibitor Kazal type 5 (SPINK5) by qRT‐PCR. Results: TGase2 was higher (P=0.0046) and TGase5 was lower (P=0.0008) in cholesteatoma than in the postauricular skin. Immunoreactivity for isopeptide bonds was localized in the granular and horny layers, and was not different between the two tissues. Immunoreactivity for CDSN was localized in the granular layer, and was lower in cholesteatoma than in the skin (P=0.0090). Western blot and qRT‐PCR confirmed that the expression of CDSN was lower in cholesteatoma than in the skin. Expressions of KLK5, KLK7, KLK14, or SPINK5 were not different between the two tissues. Conclusions: These results indicate that the production of CDSN is likely to be suppressed in cholesteatoma, which would account, at least in part, for the mechanical fragility and increased permeability of the cholesteatoma epithelium.